Soil carbon mineralization affected by hot water and ultrasound pretreatment - Toan Nguyen-Sy; Van Thanh Thi Do; Dong Pham Duy (Universitas Sebelas Maret, 2022)
Paddy soil has attracted several studies; however, the effects of pretreatment on soil carbon mineralization remain unclear. This study aimed at validating the effects of soil pretreatment by performing anaerobic incubation of 15 soil samples before treating at room temperature water boiling at 80°C or ultrasound assist at 37Hz and combining (hereafter are control, hot water, ultrasound, mixed hot water, and mixed ultrasound treatments) conducted with three replications. Results showed that initial extracted carbohydrate and incubation extracted carbohydrate (Ini-ECH and Incu-ECH) ranged from 211 to 691 mg kg−1 and 229 to 961 mg kg−1, respectively, and reached the highest values with hot water. control, ultrasound, and mixed ultrasound treatments showed the lowest Ini-ECH (211–269 mg kg−1), while the lowest Incu-ECH was linked to both mixed soil treatments with similar amounts (229–264 mg kg−1). Conversely, soil carbon mineralization (generated extracted carbohydrates during anaerobic incubation, Min-ECH) was similar in control, hot water, and ultrasound treatments (ranged from 271 to 393 mg kg−1) but tended to be a negative value in mixed soil treatments. Therefore, we conclude that hot water and ultrasound pretreatments do not increase soil carbohydrate potential but likely promote carbon decomposition.